Peran Pemerintah Mendukung Pengembangan Sport Tourism: Studi Literatur Review - Nabila, Khairan Nabila; Prayuda, Ade; Fahruzi1, Arfan Dwi (Journal of Sharia Economy and Islamic Tourism, 2024)
Abstract: This research aims to increase the attractiveness of the local economy through the promotion and development of sports as part of the tourism industry. The government has an important role in supporting the development of sports tourism as part of an economic and social development strategy. The research method used is Literature Study, literature study is a method collecting data by searching for and reading existing written sources such as books or literature that explain the theoretical basis, as well as collecting data and information by exploring knowledge or knowledge from sources such as books, written works, and several other sources that has something to do with the research object. The results of the government's role in supporting sport tourism developers show that sport tourism can be an effective strategy for increasing the attractiveness of the local economy, encouraging social development, and strengthening cultural identity. With support from the government, private sector and local communities, sport tourism can become an important sector in tourism development in Indonesia.Abstrak: Penelitian ini bertujuan untuk meningkatkan daya Tarik ekonomi lokal melalui promosi dan pengembangan olahraga sebagai bagian dari industri pariwisata.Pemerintah memiliki peran penting dalam mendukung pengembangan sport tourism sebagai bagian dari strategi pembangunan ekonomi dan sosial.Metode penelitian yang digunakan ialah Studi literatur review,studi literatur review merupakan metode pengumpulan data dengan cara mencari dan membaca sumber-sumber tertulis yang ada seperti buku atau literatur yang menjelaskan tentang landasan teori,Sama halnya dengan pengumpulan data dan informasi dengan cara menggali pengetahuan atau ilmu dari sumber sumber seperti buku, karya tulis, serta beberapa sumber lainnya yang ada hubungannya dengan objek penelitian.Hasil dari peran pemerintah dalam mendukung pengembang sport tourism menunjukkan bahwa Sport tourism dapat menjadi strategi yang efektif untuk meningkatkan daya tarik ekonomi lokal, mendorong pembangunan sosial, dan memperkuat identitas budaya. Dengan dukungan pemerintah, sektor swasta, dan masyarakat lokal, sport tourism dapat menjadi salah satu sektor penting dalam pembangunan pariwisata di Indonesia.